A plithogenic based neutrosophic analytic hierarchy process framework to analyse the barriers hindering adoption of eco-innovation practices in supply chain - Zulfiquar N. Ansari; Ravi Kant (International Journal of Sustainable Engineering, 2021)
Eco-innovations have become an essential component to attain sustainability in the supply chain. However, the process of transition from the traditional supply chain to an eco-innovative focused supply chain is faced with several challenges especially in the developing nations. Hence, this study is undertaken to evaluate the eco-innovation implementation barriers in the supply chain. A plithogenic-based neutrosophic analytic hierarchy process is used to determine the weight intensity of the barriers. Findings of the study indicate that lack of internal funds necessary to meet the extra cost and research and development cost are the major barrier in the adoption of eco-innovation initiatives. The other important barriers hindering the adoption of eco-innovation initiatives include the absence of complementary assets (such as infrastructure, standards), lack of collaboration agreements with other organisations, and high costs involved in the transition to new technologies. A manufacturing case industry is selected to apply the proposed framework. This study will help the industry experts/policy-makers to understand the important barriers hindering the adoption of eco-innovation initiatives.